2018
DOI: 10.1002/tox.22692
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of metal oxide nanoparticles and mixed exposures at low doses using zebra fish and THP1 cell line

Abstract: Metal and metal oxide nanoparticles are being used in different industries now‐a‐days leading to their unavoidable exposure to humans and animals. In the present study, toxicological testing was done using nanoparticles of copper oxide, cerium oxide and their mixture (1:1 ratio) on zebra fish embryos and THP‐1 cell line. Zebrafish embryos were exposed to 0.01 μg/ml to 50 μg/ml concentrations of dispersed nanoparticles using a 96 well plate and their effects were studied at different hours post fertilization (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…This study interestingly points out the detrimental effects of both green and chemically synthesized ZnO NPs and GO NPs on the growth and development, crawling and climbing ability of the flies as well as their cytotoxic potential at predefined concentrations, surprisingly highlighting the toxic effects of green nanoparticles. Similar to previous studies [[50], [51], [52]], we observed that the mortality rate as well as the cell viability of the flies were affected in a dose-dependent and time dependent manner.…”
Section: Discussionsupporting
confidence: 90%
“…This study interestingly points out the detrimental effects of both green and chemically synthesized ZnO NPs and GO NPs on the growth and development, crawling and climbing ability of the flies as well as their cytotoxic potential at predefined concentrations, surprisingly highlighting the toxic effects of green nanoparticles. Similar to previous studies [[50], [51], [52]], we observed that the mortality rate as well as the cell viability of the flies were affected in a dose-dependent and time dependent manner.…”
Section: Discussionsupporting
confidence: 90%
“…However, in the case of zebra fish, settling of nanoparticles will inhibit their interactions with zebra fish embryos as after 72 h of fertilization, the zebra fish embryos hatch out of the chorion and start swimming in the medium, thereby limiting the effective concentration of exposure. Moreover, for in vivo effect the role played by immune defenses from zebra fish embryos/whole organism can also not be ruled out in comparison to in vitro system [33]. The observations of the present study thus pointed towards effectiveness of functionalization of MWCNTs towards weakening the toxicity of pristine MWCNTs under in vitro versus in vivo system.…”
Section: Discussionmentioning
confidence: 72%
“…The deposition of such nanoparticles in the lungs can cause pulmonary toxicities [73]. The neurotoxicological analysis and various toxicity assessment assays performed on model organisms like zebrafish, Drosophila melanogaster and cell lines using different forms of nanoparticles are clear indicative of need of these tests before nanomedicines are released in the market [74][75][76]. The aerosolization of solutions should be avoided during solution preparation to prevent this undesired exposure.…”
Section: Environmental Safety: Money At the Cost Of Healthmentioning
confidence: 99%